ANALISIS PENGARUH LOANTA, LTA, AU, IER, EQTA, EQL DAN CIR TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH DI INDONESIA (Studi Kasus pada Bank Umum Syariah Yang Terdaftar di Otoritas Jasa Keuangan Tahun 2008 – 2018) - Abi Kumalasari, Irmadela; Hersugondo, Hersugondo (Faculty of Economics and Business Diponegoro University, 2020)
Islamic banks have been known as banks that are resistant to global The crisis that hit Indonesia a few years ago. Some Islamic bank performance can be obtained from its profitability. There are several factors that increase the profitability of Islamic banks and used in this study including Loans to Total Assets Ratio (LOANTA), Total Liabilities to Total Aseets Ratio (L/TA), Asset Utilization (AU), Income Expense Ratio (IER), Total Equity to Total Assets (Eq/TA), Total Equity to Total Liabilities (Eq/L) and Cost to Income Ratio (CIR). The purpose of this study was to determine the effect of Loans to Total Assets Ratio (LOANTA), Total Liabilities to Total Aseets Ratio (L/TA), Asset Utilization (AU), Income Expense Ratio (IER), Total Equity to Total Assets (Eq/TA), Total Equity to Total Liabilities (Eq/L) and Cost to Income Ratio (CIR) toward Profitability in Islamic Banks in Indonesia wich were proxied Return on Assets (ROA). The sampling technique used in this study is purposive sampling technique with the criteria of Islamic Banks who publish quarterly financial reports periodically during 2008 â€“ 2018. The data used in this study was obtained from annual reports on the website of Islamic Banks with a sample of elevan Islamic Banks. Methods of data analysis in this study with Multiple Regression Analysis, which previously performed classical assumption test. Hypothesis testing using Fstatistic test, t-statistical test and the determination of coefficients Adjusted ð‘… 2 with a significance level of 5%. The results of this study indicate that Loans to Total Assets Ratio (LOANTA) and Income Expense Ratio (IER) have a positive and significant effect on ROA. Total Equity to Total liabilities (Eq/L) and Cost to Income Ratio (CIR) have a positive and no significant effect on ROA. Total Liabilities to Total Aseets Ratio (L/TA) and Total Equity to Total Assets (Eq/TA) has a negative and significant effect on ROA. Asset Utilization (AU) has a negative and no significant effect on ROA.